Hereditary tumors in children - nephroblastoma - Tołoczko-Grabarek, Aleksandra; Jakubowska, Anna; Górski, Bohdan; Cybulski, Cezary; Kamieńska, Elżbieta; Lubiński, Jan; Zajączek, Stanisław; Dębniak, Tadeusz (Contemporary Oncology/Współczesna Onkologia, 2002)
A strong familiar cancer aggregation, or a congenital or genetic disorder associated with an increased risk of cancer is recognized in approximately 10-15% of childhood tumors. The cancers that occur in disorders such as xeroderma pigmentosum, ataxia teleangiectasia, Bloom syndrome, Beckwith-Wiedemann syndrome are generally secondary phenotypic manifestations to other physical stigmata of these disorders. Some cancer syndromes, such as hereditary retinoblastoma, Li-Fraumeni, familiar adenomatous polyposis coli are recognized only by their malignant manifestations with nonmalignant characteristics being virtually absent. Wilms' tumor is the most common malignant renal tumor of childhood. About 10% of Wilms' tumors occurs in individuals with congenital anomalies such as cryptorchidism/hypospadias, hemihypertrophy, or malformation syndromes, particularly Denys-Drash (DDS), WAGR (Wilms' tumor, aniridia, genitourinary anomalies, mental retardation), Beckwith-Wiedemann (BWS) syndromes which usually arise as de novo events. DDS is caused by point mutations in zinc finger region of WT1 gene and is characterized by ambiguous genitalia, diffuse mesangial sclerosis and Wilms' tumor. Patients with a deletion of WT1 gene develop WAGR syndrome. Mutations in WT2 locus are associated with pathogenesis of BWS, which is characterized by pre- and postnatal overgrowth, macroglossia and anterior abdominal wall defects. Variable complications of BWS include organomegaly, hypoglycemia, hemihypertrophy, genitourinary abnormalities, and, in about 5% of children embrional tumors. Familiar predisposition to nephroblastoma is rare, affecting only 1-2% of individuals with Wilms' tumor. The susceptibility is an autosomal dominant trait with incomplete penetrance. The fact that only some familiar cases are caused by WT1 or WT2 mutations, or show linkage to FWT1 or FWT2 loci implies the existence of additional Wilms' tumor susceptibility genes. Diagnosis of a predisposition to Wilms' tumor is based on analysis of clinical and pedigree data that enables identification of familiar nephroblastoma and also malformations/syndromes associated with a higher risk of the tumor. Diagnosis of the syndromes conferring a risk of Wilms' tumor may be facilitated by detection of germline mutations in WT1 gene (DDS and WARG), germline p57 mutations (familiar BWS), and rearrangements or paternal uniparental disomy 11p15 (BWS). The screening protocol for nephroblastoma in families with aggregation of Wilms' tumors and children with syndromes associated with a significant risk of Wilms' tumor is an abdominal ultrasound examination every three months at least until eight years of age, with the addition of computerized tomography or magnetic resonance imaging (MRI) in patients with an indeterminate lesion(s) or nephrogenic rest(s). BWS patients require additional surveillance for hepatoblastoma and neuroblastoma.